Um método para quantificar o estoque em processo à luz da simulação computacional e da análise multicritério - Pergher, Isaac (Universidade do Vale do Rio dos Sinos, 2011)
In intermittent productive systems that operate in the condition 'make to stock' with convergent flow, the possibility of generate work in process (WIP), finish good products or raw materials inventories can increase the degree of complexity of the management in the operations and the need of using procedures of different control for each stock type. Focusing in the alignment of the stocks to the demand and capacity plans, considering a productive system which uses the Conwip approach, this research describes a structured method that aims to quantify the level of WIP in the productive system, applying the Events Discrete Simulation and the technique nominated ELECTRE TRI. This research intends to contribute with the generation of information for decision support regarding the choice of work in process and finished goods stock levels, considering the production mix studied. Based in the proposal developed in this work, the Method of Research can be characterized, regarding the technical procedures, as Computational Simulation, and regarding the nature of the data, as Quantitative Research. The method proposed in this research was evaluated for specialists in the disciplines of Simulation, Administration of Production Systems and Multicriteria Decision Analysis. An application of the method in a real productive system is also presented.
Keywords: Simulação por eventos discretos; Conwip; ELECTRE TRI; Discrete event simulation; ACCNPQ::Engenharias::Engenharia de Produção